“I’m A Stripper, Ho": The Sonics of Cardi B’s Ratchet, Diasporic Feminism - Jaime, Karen (Performance Matters, 2022)
In this article, the author attends to how performer Cardi B employs urban vernacular aesthetics to articulate a ratchet, diasporic feminism. Beginning with her early Instagram videos and participation in Love and Hip Hop: New York and followed by her commercially successful song “Bodak Yellow,” Cardi B mobilizes her work between diverse musical genres and sonic registers, challenging listeners and the music industry to find room for the particularities of her ethnic and racial identity and the type of feminist practice she lyrically articulates. The author interrogates how Cardi B’s chart-topping songs, Instagram videos, and interviews on talk shows and online operate as sonic strategies that challenge, disrupt, and reject respectability politics. In turn, the author highlights how Cardi B engages with gender, class, and sexuality, proudly claiming her positionality as a former erotic dancer/stripper in order to craft a sonic narrative, framing her current success as predicated on her diligent work ethic and immigrant roots.